Reproductive Indeterminacy and Rights Discourse in Frozen Embryo Disputes - Knouse, Jessica (Columbia Journal of Gender and Law, 2022)
The lived experience of reproduction is infused with indeterminacy. Judicial rhetoric, in contrast, operates in absolutes. Litigants are perceived in binary terms as fertile or not, trying to procreate or not, pregnant or not, and parents or not – when the reality of their situations is far more complicated. Rights are similarly perceived in binary terms, such that a litigant seeking procreative autonomy may assert either the “right to procreate” or the “right to avoid procreation” – even if neither accurately describes what she wants. Disputes over frozen embryos provide unique insight into this problem, because they involve parties who have experienced months if not years of reproductive indeterminacy and who, at the point of litigation, make opposing rights claims. When a couple disagrees about the disposition of jointly-created frozen embryos and the disagreement is not resolved by contract, most courts apply a balancing test: The interests of the party asserting the “right to procreate” are weighed against the interests of the party asserting the “right to avoid procreation.” Ordinarily, the latter prevails, unless the party wishing to procreate lacks a “reasonable” path to parenthood without the embryos. Whether a “reasonable” path exists often turns on whether the party wishing to use the embryos is perceived as fertile, in which case her claim will likely be denied, or sterile, in which case it may succeed. This framework misses the complexity, contingency, and uncertainty intrinsic in all reproductive endeavors. The decision to procreate or avoid procreation is rarely singular or stable. People undergoing IVF are rarely either fertile (able to establish a pregnancy) or sterile (permanently unable to establish a pregnancy). They are, instead, infertile, and their infertility has led them to make many decisions over the course of many months and often years about how, when, and whether to proceed with treatment. And if they achieve pregnancy – not to mention parenthood – they will make many more. To describe these individuals, in the context of a frozen embryo dispute, as choosing “to procreate” or “to avoid procreation” trivializes the complexity of their circumstances. Similarly, to assume that a party experiencing infertility has a “reasonable” path to parenthood without the embryos is to ignore the reality that, even if she has the resources (physical, emotional, and financial) to undergo further treatment, there is no guarantee that it will produce gametes, that the gametes will create embryos, that the embryos will lead to pregnancy, or that the pregnancy will result in childbirth. Existing judicial rhetoric, by erasing inherent indeterminacy, offers a disappointingly limited vision of reproductive potential and reproductive rights. This article draws on multiple lines of work, from postmodern feminism to reproductive justice, to argue for a new doctrine in which reproductive rights exist not within a binary system but rather along a multi-dimensional spectrum.